Macular microcirculation changes after repair of rhegmatogenous retinal detachment assessed with optical coherence tomography angiography: A systematic review and meta-analysis - Chen, Xiaofei; Li, Wanyue; Jin, Xin; Zhang, Ying; Li, Runpu; Liu, Tiecheng (Frontiers in Physiology, 2022)
Purpose The aim of the study was to investigate microcirculation changes in the macula evaluated by optical coherence tomography angiography (OCTA) in patients receiving anatomical repair after surgery for rhegmatogenous retinal detachment (RRD). Methods A literature search was conducted in PubMed, EMBASE, Web of Science and the Cochrane Library. Studies including patients with macula-on or macula-off RRD and repaired successfully through primary surgery were selected. Foveal avascular zone (FAZ) area and macular vascular density (VD) in both the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were analyzed using RevMan 5.4 software. Results Twelve studies including 430 RRD eyes and 430 control eyes were selected. In eyes with macula-on RRD, FAZ area, VD in the foveal SCP and DCP, and VD in the parafoveal SCP and DCP were not altered compared with control eyes, after the retina was reattached. In eyes with macula-off RRD that was repaired successfully through surgery, FAZ area in the DCP (0.13 mm2, 95% CI: 0.02 to 0.25, P = 0.02) remained enlarged compared with control eyes. Meanwhile, VD in the foveal DCP was also significantly reduced (-3.12%, 95% CI: -6.15 to -0.09%, P = 0.04), even though retinal reattachment was achieved by surgery in eyes with macula-off RRD. Conclusion In patients with macula-off rhegmatogenous retinal detachment, foveal avascular zone area in the deep capillary plexuses was enlarged and vascular density in the foveal deep capillary plexus was reduced, even after the retina was successfully reattached through a primary surgery.